Role of glucose as a modulator of anabolic and catabolic gene expression in normal and osteoarthritic human chondrocytes - Rosa, SC (2011)
Cartilage matrix homeostasis involves a dynamic balance between numerous signals that modulate chondrocyte functions. This study aimed at elucidating the role of the extracellular glucose concentration in modulating anabolic and catabolic gene expression in normal and osteoarthritic (OA) human chondrocytes and its ability to modify the gene expression responses induced by pro-anabolic stimuli, namely Transforming Growth Factor-β (TGF). For this, we analyzed by real time RT-PCR the expression of articular cartilage matrix-specific and non-specific genes, namely collagen types II and I, respectively. The expression of the matrix metalloproteinases (MMPs)-1 and -13, which plays a major role in cartilage degradation in arthritic conditions, and of their tissue inhibitors (TIMP) was also measured. The results showed that exposure to high glucose (30 mM) increased the mRNA levels of both MMPs in OA chondrocytes, whereas in normal ones only MMP-1 increased. Collagen II mRNA was similarly increased in normal and OA chondrocytes, but the increase lasted longer in the later. Exposure to high glucose for 24 h prevented TGF-induced downregulation of MMP-13 gene expression in normal and OA chondrocytes, while the inhibitory effect of TGF on MMP-1 expression was only partially reduced. Other responses were not significantly modified. In conclusion, exposure of human chondrocytes to high glucose, as occurs in vivo in diabetes mellitus patients and in vitro for the production of engineered cartilage, favors the chondrocyte catabolic program. This may promote articular cartilage degradation, facilitating OA development and/or progression, as well as compromise the quality and consequent in vivo efficacy of tissue engineered cartilage.